2021
DOI: 10.1038/s41586-021-03519-x
|View full text |Cite
|
Sign up to set email alerts
|

A high-quality bonobo genome refines the analysis of hominid evolution

Abstract: The divergence of chimpanzee and bonobo provides one of the few examples of recent hominid speciation1,2. Here we describe a fully annotated, high-quality bonobo genome assembly, which was constructed without guidance from reference genomes by applying a multiplatform genomics approach. We generate a bonobo genome assembly in which more than 98% of genes are completely annotated and 99% of the gaps are closed, including the resolution of about half of the segmental duplications and almost all of the full-lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 38 publications
2
64
3
Order By: Relevance
“…Reads were not available for the genome assembly from which bonobo CEACAM sequences were identified for the evolutionary analyses described here. However, a more recent assembly of a different bonobo individual became available during the course of this study and sequencing reads for this new de novo assembly were deposited ( Mao et al, 2021 ). The CEACAM1 genomic region of the newer assembly was 99% identical to the older version while the coding sequences differ at only a single nucleotide outside of the N-domain.…”
Section: Methodsmentioning
confidence: 99%
“…Reads were not available for the genome assembly from which bonobo CEACAM sequences were identified for the evolutionary analyses described here. However, a more recent assembly of a different bonobo individual became available during the course of this study and sequencing reads for this new de novo assembly were deposited ( Mao et al, 2021 ). The CEACAM1 genomic region of the newer assembly was 99% identical to the older version while the coding sequences differ at only a single nucleotide outside of the N-domain.…”
Section: Methodsmentioning
confidence: 99%
“… Kronenberg et al (2018) generated the genome assemblies of human, chimpanzee, and orangutan using SMRT long-read sequencing with over 65-fold coverage. Mao et al (2021) reported a new high-quality bonobo genome assembly using the long-read PacBio platform with 74-fold sequence coverage. The details of recently assembled genomes of great apes can be found in Table 1 .…”
Section: Genome Assembliesmentioning
confidence: 99%
“…They also found that the small past Ne correlates with a larger number of deleterious alleles and the genes enriched with bonobo-specific non-synonymous changes are related to age at menarche in humans. Based on a new bonobo genome assembly, Mao et al (2021) identified some novel genes and found that most of the novel genes showed selective sweeps in bonobo, such as DIRC1 , GULP1 , and ERC2 .…”
Section: Natural Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonobo genomic DNA was not available for direct sequencing of CEACAM1, so currently available bonobo genome sequence data was used for sequence verification. While the genome assembly from which bonobo CEACAM sequences were identified for evolutionary analyses did not have reads available, a more recent assembly of a different bonobo individual became available during the course of this study which did deposit sequencing reads along with a de novo genome assembly (Mao et al, 2021). The CEACAM1 1 genomic region of the newer assembly was 99% identical to the older version while the coding sequences differ at only a single nucleotide outside of the N-domain.…”
Section: Bonobo Ceacam1 N-domain Sequence Verificationmentioning
confidence: 99%